A propósito del Covid-19. El rol de la edad y género en la inmunidad - González Campos, Óscar (Revista Hospital Clínico Universidad de Chile, 2020)
The purpose of the immune system is to protect the body from pathogenic microorganisms such as bacteria, viruses, fungi and even tumor cells, which could cause disease. When the encounter with pathogens occurs, defenses are produced immediately through the innate response, faster and more nonspecific, and through the adaptive response, more defined and personalized for each attacker. Both are triggered by the cells of the immune system being able to communicate with each other, once they have been activated. The innate immune system works in tune with the acquired immune system through the close intervention of the sex hormones, with specific strategies of estrogen and progesterone. Both have a proven anti-inflammatory and antioxidant action not only at the level of the wall of blood vessels, skin and mucous membranes, but also in the protection of the central nervous system against all toxic agents, such as viruses. Estrogens and progesterone play an essential role in the immune response and its evolution, and although they initially appear as antagonistic responses, they are not, despite the fact that estrogens increase and progesterone seems to suppress the immune response, depending on the immune target according to the case.